PELATIHAN PEMBUATAN BLACK GARLIC SEBAGAI PANGAN FUNGSIONAL PEMELIHARA KESEHATAN BAGI KELOMPOK PENGAJIAN AL IHSAN, PEDURENAN, TANGERANG - Muhamad Alif Razi; Nanang Alamsyah; Fajri Ashfi Rayhan (Gapenas Publisher, 2022)
Covid-19 pandemic has made a negative impact on the health status of many people in Indonesia. While vaccination is a great tool for decreasing the infection rate and increasing the survival rate, consuming functional foods and vitamins is also beneficial for increasing the body immunity and maintaining a good health. Black garlic is one of the functional foods derived from garlic. Black garlic has many beneficial health effects such as reducing blood pressure and cholesterol, thereby reducing the risk of getting heart disease and stroke. In addition, Black garlic has a good antioxidant compound which can increase the body immunity and reduce oxidative stress. In order to disseminate the health benefits of black garlic, we conduct training on making black garlic to Al Ihsan religious group in Pedurenan, Tangerang City.